Caracterização e investigação da atividade leishmanicida de nanocarreadores complexados com antimônio e/ou quercetina - Menezes, Janaína Barros de (2018)
Considering the severity of leishmaniasis as a world-wide anthropozoonosis (category I of the Tropical Diseases Program, referring to emerging and out-of-control diseases, according to the World Health Organization) and in the national context; the reemergence of the disease due to Leishmania-HIV co-infection; and the chemotherapeutics indicated for the treatment of the disease, which, although effective, are endowed with severe adverse effects, justify the search for alternatives. The objective of this work was to investigate the use of inorganic nanomaterials as Lamellar Double Hydroxides (HDLs), synthesized by co-precipitation, as two-dimensional host matrices of SbIII and / or quercetin to evaluate their leishmanicidal activity. The binary systems (QUE-SbIII, Mg, Al HDL-QUE and Mg, Al / Sb HDL-QUE) and ternary [HDL- (QUE-SbIII)] are synthesized via solution (co-precipitation) and characterized. UV-Vis spectrophotometry allows visualization of the interaction between quercetin and the metals of HDL by observing bathochromic shift in the quercetin band, which confirms its chelation with (semi-) metals and the consequent formation of new products; as well as the appearance of fluorescence in the binary and ternary systems, ratifying the interaction of quercetin with the (semi-) metals present. Fourier Transform Infrared Spectrometry (FTIR) suggests the quercetin: carbonyl metal bonding sites of positions C-3 and C-4 in the binary system Mg, Al HDL-QUE and the ternary system HDL-(QUE-SbIII); and in binary systems QUE-SbIII and Mg, Al HDL-QUE, in addition to the carbonyl region, ortho-phenolic chelation of the B-ring in the quercetin molecule. X-Ray Diffraction (XRD) determines the success in the synthesis of binary and ternary nanosystems in order to obtain products with different crystallinity, where the leishmanicidal drugs have associated with the nanocarrier. Finally, the thermogravimetry (TG) traced the degradation profile of the obtained systems. In view of this, we can confirm the formation of the binary and ternary nanosystems suggested, and thus, we can affirm that the obtained products present a potential application to the treatment of leishmaniasis; which was confirmed by the in vitro leishmanicidal activity, with emphasis on Mg, Al / Sb HDL-QUE and HDL- (QUE-SbIII), which showed little toxicity to macrophages and good leishmanicidal activity for promastigotes of L. amazonensis and promastigotes of L. chagasi.